Pemanfaatan Media Sosial Sebagai Sarana Promosi UMKM “Sang Telang” - Falery Febianti; Chrystia Aji Putra; Chory Aura Nurtyara; Sri Rahmayanti; Fauziyah Herdatul Dwi Krisdayanti; Achmad Muhaimin Nur Khafi (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The government has always supported various uses of digital-based technology aimed at increasing the productivity of MSMEs. MSME actors can expand their product marketing through the digital world or online, this is expected to accelerate the change of MSMEs in Indonesia towards digital. However, not all products issued by MSMEs can be widely known, especially by the public. The main reason is that they have not maximized the use of social media as a means of promotion. The purpose of this study is to find out what benefits make social media used as a means of promotion for business, especially for SMEs. The method used in this research is a qualitative method, which is a method that tries to explain and analyze phenomena, events, social dynamics, behavior, and the perception of a person or group of something. Utilization of social media for business actors can provide advantages, among others as a means of promotion or marketing, can establish relationships with consumers through personal contacts, can be used as consumer data collection, can convey information or responses to consumers. Social media has many benefits for most MSME actors in promoting their products. If social media has become part of the daily life of MSME actors as a means of promotion, then MSME products will be widely known by the public.